Pembuktian Isu Kehilangan BBM Head Truck Depo Transhipment Pada PT. Berkah Multi Cargo Logistic - Hermawan, Budi; Faris Indriya Himawan, Abdurrahman (Rifa'Institute, 2022)
Head truck activities at PT. BMC Logistics is currently experiencing the issue of fuel consumption which is considered too wasteful, therefore it is suspected that there is a theft of fuel in the fuel tank. This study aims to prove the issue of fuel loss caused by theft by calculating the average fuel consumption (liters / hour) on each head truck every day with a sample of 15 head truck units located at the transshipment depot of PT. BMC Logistics which is located on Jalan Perak Utara, Pabean Cantian, Surabaya, East Java 60165. The research uses quantitative methods by collecting data based on a daily head truck checklist data sample from July 2021 to October 2021, then an average consumption of Liters per hour is made from the initial fuel filling to the next fuel filling, then a normality test is carried out to find out whether H0 (theft did not occur) is accepted or rejected. From the results of the study it was found that the test data were normally distributed. which means that the issue of fuel theft really didn't happen.